Three-Dimensional Surgical Guides in Orthodontics: The Present and the Future - Silvia Izabella Pop; Eugen Bud; Kinga Mária Jánosi; Anamaria Bud; Bernadette Kerekes-Máthé (Dentistry Journal)
Surgical guides are integral tools in orthodontics, enhancing the precision and predictability of mini-implant placement. These guides facilitate accurate positioning, reduce risks to surrounding anatomical structures, and ensure proper angulation and depth during procedures. The aim of the present paper is to present a detailed review of the surgical guides used in orthodontics, focusing on their classification, mechanical properties, biocompatibility, and future developments. The advantages, disadvantages, clinical steps, and implications are also described based on the data in recent scientific literature. Future developments may incorporate artificial intelligence and augmented reality, further optimizing treatment planning and patient outcomes, thus solidifying the role of surgical guides in efficient orthodontic care.